HOLLOWNESS OF CIVILIZED SOCIETY IN THE NOVEL THE APPRENTICE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
In the novel The Apprentice, the depiction of a civilised society serves as a critical backdrop against which the protagonist’s journey unfolds. The protagonist enters a world where rules, order, and societal norms dictate behaviour and interactions. This civilised society starkly contrasts the protagonist’s upbringing and challenges the protagonist’s beliefs and values. The protagonist confronts societal expectations in a novel that examines the complexities of a civilised society, questioning traditional norms and values. This paper investigates how the author portrays this society and its key traits, reflecting or contrasting with real-world societies to reveal underlying critiques. A central theme of hollowness permeates the narrative, highlighting the emptiness within the characters and their environment. Through a detailed analysis of key events and moments, the paper aims to uncover deeper meanings and the commentary on human nature within a structured society.